2018
DOI: 10.31661/jbpe.v8i4dec.768
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Gamma-H2AX Expression as a Biomarker of DNA Damage after X-ray in Angiography Patients

Abstract: Objective: Coronary heart disease (CHD) is one of the most common diseases. Coronary angiography (CAG) is an important apparatus used to diagnose and treat this disease. Since angiography is performed through exposure to ionizing radiation, it can cause harmful effects induced by double-stranded breaks in DNA which is potentially life-threatening damage. The aim of the present study is to investigate phosphorylation of Histone H2AX in the location of double-stranded breaks in peripheral blood lymphocytes as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(39 reference statements)
1
8
1
Order By: Relevance
“…Among the three biomarkers used, the γ-H2AX foci assay, demonstrated a positive correlation between the frequency of γ-H2AX foci and the fluoroscopy time (r = 0.520 and p = 0.013) and a linear positive correlation between the frequency of γ-H2AX foci and effective dose (r = 0.540 and p = 0.010). This result is in accordance with earlier studies that reported a positive correlation in patients exposed to low radiation doses (35,36).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Among the three biomarkers used, the γ-H2AX foci assay, demonstrated a positive correlation between the frequency of γ-H2AX foci and the fluoroscopy time (r = 0.520 and p = 0.013) and a linear positive correlation between the frequency of γ-H2AX foci and effective dose (r = 0.540 and p = 0.010). This result is in accordance with earlier studies that reported a positive correlation in patients exposed to low radiation doses (35,36).…”
Section: Discussionsupporting
confidence: 94%
“…At a molecular level, there are certain studies that report an increase of DSBs after exposure to low ionizing radiation doses. Kuefner et al (34) and Alipoor et al (35) observed an increase in the percentage of DSBs after exposure to angiography, compared to pre-exposure time. Similarly, in our study, not only a statistically significant increase in the mean value of DNA DSBs was observed for the total study group, but also at the individual level, this increase was statistically significant in the 91% of patients after their cardiac interventional procedures and residual γ-H2AX foci were still detectable in irradiated lymphocytes, 24 h after.…”
Section: Discussionmentioning
confidence: 97%
“…ATR activation facilitates chemotherapy resistance to cisplatin, 16,26,27 and ATR inhibition enhances cisplatin chemosensitivity. 9,28,29 In this study, we found that blocking ATR with the inhibitor VE-822 or with ATR shRNA upregulated the phosphorylation of H2AX, a biomarker of DNA damage, 30,31 indicating that ATR inhibition promoted cisplatin-induced DNA damage. As expected, ATR inhibition promoted cisplatin-induced inhibition of cell proliferation and cell death in chondrosarcoma cells, suggesting that VE-822 mediated inhibition of ATR is a valuable strategy for chemotherapy of chondrosarcoma with cisplatin.…”
Section: Discussionmentioning
confidence: 60%
“…γ-H2AX is a DNA repair protein whose expression is commonly measured to quantify double-stranded DNA damage [ 43–45 ]. Compared with that in the control group, the expression of γ-H2AX in the 1 mM bup group was not significantly different; however, 2 mM bup increased γ-H2AX protein expression ( Figure 2 A&B).…”
Section: Resultsmentioning
confidence: 99%